Influence of the sizes of crystals on edge radiation in unalloyed gallium arsenide - Штанько, Александр Дмитриевич; Литвинова, Марина Борисовна (Eastern-European Journal of Enterprise Technologies, 2012)
The sizes of surface of the samples, which were cut out from undoped GaAs crystals with surplus of gallium and with surplus of arsenic, when influence of mechanical stress on energy position of the maximum of the edge radiation band at 77 K can be neglected are determined